SAFETY AND HEATH EVALUATION OF THE GAS EXPOSURE IN THE AREA OF EFFLUENT WATER TREATMENT PLANT (ETWP) OF PT. X - Muhammad Isradi Zainal; Andi Surayya Mappangile; Muhammad Suryo Hadi Rivai (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Objective of the research is to evaluate the safety and health of gas exposure in the area of Effluent Water Treatment Plant (ETWP) of PT. X. Methods used to evaluate the safety and health of gas exposure based on Permenaker  No. 5/2018, which stated that if there is more than one chemical substance in the air in the work environment, the Treshold Limit Value (TLV) is mixed, the mixture of these chemicals can be determined by calculating the ratio between the levels of the chemical substance with the TLV, if the result of calculation exceeds 1 (> 1) then it is considered passed the TLV of the mixture (unsafe). The Results of the research in the three areas of the unit showed that the mixed TLV has exceeded the value of 1 (>1) and there were 2 out of 4 informants who had health complaints due to the gas exposure namely shortness of breath. Conclusions The gas exposure in 3 areas of the Sludge Treatment Unit (DAF Scum Sump, Sludge Coagulator, Drying Box) in the first, second and third measurements did not meet the Mixed Threshold limit Value (Mixed TLV) requirements based on the Minister of Manpower Regulation Number 5 Year 2018 concerning Occupational Safety and Health in the Work Environment and it can be indicated that the area is very risky. The control methods taken was engineering control, administration and Personal Protective equipment (PPE).